Bevacizumab Monotherapy or Combined with Laser versus Laser Monotherapy in Mongolian Patients with Diabetic Macular Edema - Toishubai, Anaraa; Davaatseren, Uranchimeg; Jamyanjav, Baasankhuu; Lim, Sun Taek; Tuvaan, Bulgan; Tsengenbayar, Munkhzaya; Batbileg, Munkhkhishig; Luvsantseren, Oyunzaya; Jamyansuren, Urangua; Munkhkhuyag, Munkhsaikhan; et al. (Central Asian Journal of Medical Sciences, 2016)
Objectives: To evaluate the efficacy and safety of bevacizumab monotherapy and bevacizumab therapy combined with laser therapy versus laser monotherapy in Mongolian patients with visual impairment due to diabetic macular edema (DME). Methods: One hundred twelve eligible patients, aged ^18 years, with type 1 or 2 diabetes mellitus and best corrected visual acuity (BCVA) in the study eye of 35 to 69 Early Treatment Diabetic Retinopathy Study letters at 4 m (Snellen equivalent: >6/60 or <6/12), and with visual impairment due to center-involved DME were included in the study. Patients were randomized into three treatment groups: (1) intravitreal bevacizumab monotherapy (n = 42), (2) intravitreal bevacizumab combined with laser therapy (n = 35), and (3) laser monotherapy (n = 35). Bevacizumab injections were given for three initial monthly doses and then pro re nata thereafter based on BCVA stability and DME progression. The primary efficacy endpoints were the mean change in BCVA and central retinal subfield thickness from baseline to month 12. Results: Bevacizumab monotherapy and bevacizumab + laser were superior to laser monotherapy in improving the mean change in BCVA letter score from baseline to month 12 (+8.3 and +11.3 vs +1.1 letters; both p ><0.0001). At month 12, a greater proportion of patients gained >10 and >15 letters and had a BCVA letter score >73 (Snellen equivalent: >6/12) with bevacizumab monotherapy (23.8% and 7.1% and 4.8%, respectively) and bevacizumab + laser (57.1% and 28.6% and 14.3%, respectively) versus laser monotherapy (0% and 0% and 0%, respectively). The mean central retinal subfield thickness was significantly reduced from baseline to month 12 with bevacizumab (-124.4 pm) and bevacizumab + laser (-129.0 pm) versus laser (-62.0 pm; both p = 0.002). Conjunctival hemorrhage was the most common ocular event. No endophthalmitis cases occurred. Conclusion: Bevacizumab monotherapy or bevacizumab + laser showed superior BCVA improvements over macular laser treatment alone in Mongolian patients with visual impairment due to DME.